Habilidades sociais educativas de docentes universitários na avaliação de alunos: validação de um instrumento - Santos, Joene Vieira dos (2019)
The present study had as objectives to examine: (a) evidence of validity of the Inventory of Educational Social Skills of the University Professor – Student Version (IESS-UPStudent) based on the internal structure and relationship with the satisfaction criterion variable; (b) the relationship between teacher and student evaluation of the professor’s HSE repertoire; and (c) the differences in the HSE level attributed to the teacher according to the characteristics of the sample. One thousand four hundred and six students and 16 university professors participated in this study. The results showed that IESS-UP-Student is composed of five dimensions: approve and value student behavior (AVB, 13 items), expose, explain and evaluate interactively (EEE, 11 items), cultivate affection, support and good humor (ASG, 10 items), reject undesirable student behaviors (RUB, 9 items) and guide activities (GAc, 6 items), which form a higher dimension called the university professor’s ESS. The invariance analysis of the model showed that this structure is equivalent in function of characteristics of the professor, student and Institution of Higher Education (IHE). The data also indicated that teacher’s HSE interferes positively and significantly in the level of student satisfaction with the teaching performance (variable criterion) and there are discrepancies between teachers’ and students’ perceptions of professor performance. In addition, differences in the HSE level attributed to teachers were identified according to the characteristics of the teacher (gender, role and contact in other disciplines), student (gender, area of knowledge and moment of the course) and IHE (nature, region and philosophy institutional). These results seem to indicate that the IESS-UP-Student can be a useful tool to: (a) examine the learning conditions offered to the student, based on the professor’s HSE; (b) provide feedback to the teacher about the relationship established with their students; and (c) to evaluate the effectiveness of intervention programs aimed at developing the HSE of college teachers.